2018
DOI: 10.1111/jace.16180
|View full text |Cite
|
Sign up to set email alerts
|

The effect of TiO2 additions on CaO–MgO–Al2O3–SiO2 (CMAS) crystallization behavior from the melt

Abstract: Titania (TiO2) was introduced into a model calcium‐magnesium aluminosilicate (CMAS) glass in additions of 5‐20 wt%. The crystallization behavior of the mixtures was characterized over a series of temperature profiles and compared to that of CMAS alone. X‐ray diffraction, differential scanning calorimetry, light and scanning electron microscopy, and energy dispersive spectroscopy were used to characterize glass and crystalline products. Titania additions in the amount of approximately 12.5‐20 wt% aided in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…For instance, ytterbium disilicate is preferred to yttrium disilicate for EBC applications owing to undesirable polymorphic transitions during processing in the latter. There has also been interest to develop EBCs based on REO 1.5 -TiO 2 systems, 105 and TBCs containing TiO 2 and TaO 2.5 . [106][107][108][109] While there have been some experimental studies to assess how each of these novel coating candidates reacts with CMFAS-type deposits, 22,105,108 the lack of thermodynamic models for the relevant Yb-, Ta-, and Ti-oxide subsystems complicates the implementation of models for these systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, ytterbium disilicate is preferred to yttrium disilicate for EBC applications owing to undesirable polymorphic transitions during processing in the latter. There has also been interest to develop EBCs based on REO 1.5 -TiO 2 systems, 105 and TBCs containing TiO 2 and TaO 2.5 . [106][107][108][109] While there have been some experimental studies to assess how each of these novel coating candidates reacts with CMFAS-type deposits, 22,105,108 the lack of thermodynamic models for the relevant Yb-, Ta-, and Ti-oxide subsystems complicates the implementation of models for these systems.…”
Section: Discussionmentioning
confidence: 99%
“…There has also been interest to develop EBCs based on REO 1.5 -TiO 2 systems, 105 and TBCs containing TiO 2 and TaO 2.5 . [106][107][108][109] While there have been some experimental studies to assess how each of these novel coating candidates reacts with CMFAS-type deposits, 22,105,108 the lack of thermodynamic models for the relevant Yb-, Ta-, and Ti-oxide subsystems complicates the implementation of models for these systems. There is a need to further basic scientific investigations to determine the key phase relationships and thermodynamic properties necessary to enable future extensions of the thermodynamic databases to encompass these systems.…”
Section: Discussionmentioning
confidence: 99%
“…The columnar porous structure, which is typically adopted in TBC with good thermal shielding and stress tolerance, is not suitable anymore. This is the main difference in microstructure between TBC and EBCs 48 . It raises several questions: Dense multilayer EBCs set a much more critical requirement in CTE matching between EBCs and substrates as well as among EBCs’ layers.…”
Section: Ebcs’ Stabilitymentioning
confidence: 99%
“…Solutes such as aluminium and titanium-containing compounds have been utilised in this approach. Specifically Ti 4+ ions are utilised when incorporating TiO 2 [86,118], and Al 3+ ions are used when incorporating Al 2 O 3 [81,86,119,120]. Drexler et al [119] investigate 7YSZ+Al+Ti materials in the form of bulk ceramic pellets with 15% porosity.…”
Section: Model Materials Systemsmentioning
confidence: 99%
“…Other studies have proposed a more direct role of TiO 2 if used in sufficient quantity [118]. Webster et al [118] showed that incorporating TiO 2 in quantities over 12.5 wt-% into a CMAS glass powder induces the formation of CaTiO 3 (Figure 20) as a CMAS crystallisation product in the temperature range of 1300–1500°C.…”
Section: Evaluation Of Cmas Mitigation Strategiesmentioning
confidence: 99%